Kindergarten Teachers' Perception on Preschoolers' Formative Assessment - Roxana Apostolache (Babes-Bolyai University, 2024)
Formative assessment is a primary process within the preschool education system because it contributes to the optimization of the instructional actions carried out by the teacher. Working directly with preschoolers need to lead to a constant observation of their evolution, progress, development. Assessment in early childhood should be performed for the primary aim of supplying teachers with useful information to plan more careful children's ongoing development and to involve evaluation strategies that develop rather than threaten children's feelings of self-confidence and positive social attitudes. Kindergarten teachers are important catalyst for developing opportunities to increase preschoolers' abilities, knowledge and validate/improve their performances through formative measures in terms of assessment. This study is conducted to investigate teachers' perceptions on formative assessment in kindergarten. Through a focus group we planned to gather responses of 12 kindergarten teachers, therefore our approach presents results of this analysis. At the same time, present article emphasizes on importance of using different formative instruments and methods in order to facilitate children progress and knowledge development along the way in the didactic process.